Wernicke's encephalopathy in a child with high dose thiamine therapy - So Won Park; Yoon Young Yi; Jung Woo Han; Heung Dong Kim; Joon Soo Lee; Hoon-Chul Kang (Korean Pediatric Society, 2014)
Wernicke's encephalopathy is an acute neurological disorder characterized by mental confusion, oculomotor dysfunction, and ataxia. It has been reported in individuals with alcohol dependence, hyperemesis gravidarum, and prolonged parenteral nutrition without vitamin supplementation. Here we present the case of a 13-year-old male patient with neuroblastoma and a history of poor oral intake and nausea for 3 months. After admission, he showed gait disturbances, nystagmus, and excessive dizziness; his mental state, however, indicated he was alert, which did not fit the classical triad of Wernicke's encephalopathy. A diagnosis of Wernicke's encephalopathy was made only after brain magnetic resonance imaging and serum thiamine level analyses were performed. The patient's symptoms remained after 5 days of treatment with 100-mg thiamine once daily; thus, we increased the dosage to 500 mg 3 times daily, 1,500 mg per day. His symptoms then improved after 20 days of replacement therapy. This case report describes a pediatric patient who was promptly diagnosed with Wernicke's encephalopathy, despite only 2 suspicious symptoms, and who completely recovered after high doses of thiamine were given intravenously.